2020
DOI: 10.1177/0001839220929736
|View full text |Cite
|
Sign up to set email alerts
|

Coming Back and Giving Back: Transposition, Institutional Actors, and the Paradox of Peripheral Influence*

Abstract: We explore transposition—bringing ideas from one context to a distant other context—as a mechanism for institutional change, and we study the conditions under which institutional actors successfully undertake it. Prior work on transposition has emphasized the paradox of embedded agency: actors embedded in a context may struggle to effect change because they lack exposure to fresh ideas. We complement this work by arguing that transposition is also subject to a paradox of peripheral influence: actors not embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 148 publications
1
45
0
Order By: Relevance
“…This paper takes a middle-ground approach: we resist the urge for crude generalizability because the forms and practices of leadership in any community are deeply embedded in the specific cultural fabric of that community and thus are rooted in their particular histories, identities, values and worldviews. In place of "generalizability," we prefer the term "transposability" to highlight how ideas and practices can travel across different contexts and influence one another (Luo et al, 2020;Sewell, 1992). Transposability means that ideas from one context can enter another context and lead to formation of new practices consistent with the latter context's culture and values.…”
Section: Discussionmentioning
confidence: 99%
“…This paper takes a middle-ground approach: we resist the urge for crude generalizability because the forms and practices of leadership in any community are deeply embedded in the specific cultural fabric of that community and thus are rooted in their particular histories, identities, values and worldviews. In place of "generalizability," we prefer the term "transposability" to highlight how ideas and practices can travel across different contexts and influence one another (Luo et al, 2020;Sewell, 1992). Transposability means that ideas from one context can enter another context and lead to formation of new practices consistent with the latter context's culture and values.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because they are exposed to advanced CSR and environmental practices, which is a positive incentive. For instance, Luo et al (2021) find a positive and significant association between directors' overseas experience and corporate donations. A recent study by Ullah et al (2021) finds that directors with foreign experience positively enhance the stock price informativeness in Chinese listed firms.…”
Section: Hypothesis Developmentmentioning
confidence: 93%
“…For instance, Luo et al. (2021) find a positive and significant association between directors' overseas experience and corporate donations. A recent study by Ullah et al.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…These studies have generally found that returnees, typically returning from more advanced economies to their home countries, cast a positive influence on the performance of local firms due to their possession of non-local knowledge and their ability to acquire resources more efficiently [3], especially when returnees are embedded in local networks [17]. More recently, Luo and colleagues conceptualize Chinese returnees from abroad as "institutional carriers," who are uniquely able to transfer foreign ideas (e.g., corporate social responsibility practices) to local businesses [18]. Whereas these returnee studies generally treat the level of return migration as a given, our study shows that migrants' decisions to return are non-trivial because migrants are hindered by pre-existing barriers, the lifting of which may generate new and betterperforming businesses.…”
Section: And Conclusionmentioning
confidence: 99%